Student Response to Implementation of PKM Training By BEM FIP Universitas Negeri Padang - Setiawati Setiawati (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
This research is motivated by the lack of ability of the Faculty of Education students to produce innovative scientific work. This is allegedly related to the implementation of the training carried out. The purpose of this study was to obtain an overview of the implementation of PKM training held by BEM FIP. This study was classified as quantitative descriptive, the study population was all students who took part in the 2015 PKM training, and a sample of 40 people. The sample selection technique uses cluster random sampling. The data in this study are student responses to the implementation of PKM training, and data sources are students who take PKM training. The data collection technique uses a questionnaire and the analysis technique used is the percentage. The results showed that students who took PKM training responded quite well to the implementation of PKM training conducted by BEM FIP, but for material and time needed improvement because the training material was more theoretical and minimal practical, and the need to provide time for training under the guidance of outside instructors training schedule.